1998
DOI: 10.1016/s0378-1097(98)00124-4
|View full text |Cite
|
Sign up to set email alerts
|

False positive diagnosis of meningococcal infection by the IS1106 PCR ELISA

Abstract: At a time when optimal case ascertainment for meningococcal infection is a high priority, the need for non-culture case confirmation, in particular by DNA amplification, is seen as being of vital importance to assist contact management and cluster recognition. A solution hybridisation assay with colorimetric microtitre plate detection (polymerase chain reactionenzyme-linked immunosorbent assay (PCR ELISA)) has been developed using the multicopy insertion sequence IS1106 which had reportedly achieved a specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…With this rapid turnaround time and the high positive and negative predictive values of the test, the clinician can rapidly and accurately establish or exclude a diagnosis of meningococcal meningitis. While we had only one possible false-positive result with our assay during the study and in prior testing with multiple different organisms (data not shown), it has been found by other investigators that the IS 1106 PCR assay may result in false-positive results with organisms other than N. meningitidis (1,8). This outcome may occur because of the inherent genetic mobility of insertion sequences, which may result in their transfer among bacterial species and genera.…”
mentioning
confidence: 73%
“…With this rapid turnaround time and the high positive and negative predictive values of the test, the clinician can rapidly and accurately establish or exclude a diagnosis of meningococcal meningitis. While we had only one possible false-positive result with our assay during the study and in prior testing with multiple different organisms (data not shown), it has been found by other investigators that the IS 1106 PCR assay may result in false-positive results with organisms other than N. meningitidis (1,8). This outcome may occur because of the inherent genetic mobility of insertion sequences, which may result in their transfer among bacterial species and genera.…”
mentioning
confidence: 73%
“…PCR-based detection and characterization is especially useful when treatment has been given and culture has proven negative, although the success of PCR depends largely on the gene target used [21][22][23][24]. The detection of the insertion element IS1106 can be used to confirm the presence of N. meningitidis in suspected cases, and was developed in both standard and PCR ELISA formats [23,25]. However, as insertion sequences are genetically mobile and spread between species and even genera, the IS1106 PCR can lead to false positives [25].…”
Section: Pcrmentioning
confidence: 99%
“…The detection of the insertion element IS1106 can be used to confirm the presence of N. meningitidis in suspected cases, and was developed in both standard and PCR ELISA formats [23,25]. However, as insertion sequences are genetically mobile and spread between species and even genera, the IS1106 PCR can lead to false positives [25]. Therefore, a species-specific PCR assay was developed to detect the ctrA gene [26].…”
Section: Pcrmentioning
confidence: 99%
“…Although DNA evaluation was not possible using spectrometry, near baseline absorbance at 230 nm indicated minimal contaminants in the sample (Fig 3.1C). For RNA extractions, typical yields were [30][31][32][33][34][35][36][37][38][39][40] ng/μL in a 10 μL elution with 260/280 and 260/230 ratios of 1.9-2.2 and 1.8-2.3 respectively (Fig 3.1C), indicating good purity. A key characteristic of flocculation is the abrupt transition from solution phase to flocculate which makes this phenomena ideal for binary yes/no applications.…”
Section: Resultsmentioning
confidence: 99%
“…25 This technique has been reported to successfully detect viruses 26 , bacteria 27 and fungi 28,29 with higher specificity than conventional PCR. However, despite its high specificity, the assay generated false positive results while detecting Neisseria meningitidis 30 and Mycobacterium tuberculosis 31,32 because the PCR amplified DNA was found to hybridize with the ELISA probe from other species.…”
mentioning
confidence: 99%